2008
DOI: 10.1007/s11552-008-9109-z
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment of Thumb Carpometacarpal Joint Arthritis: A Single Institution Experience from 1995–2005

Abstract: There are numerous techniques for the surgical management of thumb carpometacarpal (CMC) joint arthritis. The four senior authors of this study employ three such techniques: trapeziectomy with hematoma distraction arthroplasty, hemitrapeziectomy with osteochondral allograft, and ligament reconstruction tendon interposition (LRTI). This study examines the three commonly utilized procedures at a single institution. This study examines the 10-year experience from 1995-2005 with a minimum 3-month follow-up. Disabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 58 publications
4
50
0
2
Order By: Relevance
“…3,9 Comparative studies have shown no significant long-term difference in outcomes among these techniques, 18,[29][30][31] aside from a lower complication rate 30,31 and shorter operative time with trapeziectomy alone. 20 The use of a suture-button suspensionplasty (SBS) with trapeziectomy has grown in popularity. 6,24,35,36 Advocates of this technique cite safety, ease of use, early mobilization, and good early results.…”
Section: Surgery Articlementioning
confidence: 99%
“…3,9 Comparative studies have shown no significant long-term difference in outcomes among these techniques, 18,[29][30][31] aside from a lower complication rate 30,31 and shorter operative time with trapeziectomy alone. 20 The use of a suture-button suspensionplasty (SBS) with trapeziectomy has grown in popularity. 6,24,35,36 Advocates of this technique cite safety, ease of use, early mobilization, and good early results.…”
Section: Surgery Articlementioning
confidence: 99%
“…Currently, no single procedure has shown a clear benefit over others. 2,4,5 TightRope (Arthrex, Naples, FL) TMC suspensionplasty has been proposed as an alternative to Kirschner wire fixation that may allow for earlier mobilization in the hope of preventing stiffness and avoiding Kirschner wire complications such as pin track infection. 6,7 Yao et al 8 demonstrated that compared with Kirschner wire fixation, TightRope suspensionplasty has equivalent strength and ability to maintain trapezial space after repeated loading cycles.…”
mentioning
confidence: 99%
“…Davis and Pace (20) performed the procedure on 46 patients with an average DASH score of 37 at one year postoperatively. In another study evaluating an institution's 10-year experience, the mean DASH score was 19.26±12.94 (21).…”
Section: Discussionmentioning
confidence: 98%